Will representation targets based on area protect critical resources for the conservation of the Tucuman Parrot? - Pidgeon, Anna Michle (2015)
The Tucuman Parrot (Amazona tucumana), which is restricted to Southern Yungas forest of Argentina and Bolivia, has not recovered from severe population declines in the 1980s. We assessed habitat conservation targets for this species and asked, “What constitutes the right target?” For species with small ranges, maximizing the proportion of the range under protection is an established strategy to safeguard against threats. However, designating an amount for protection based on range alone (i.e. a ‘representation target') may set a misguided conservation target if critical resources are not considered. We used an ensemble model (‘biomod2’) to map suitable breeding and nonbreeding habitat of the Tucuman Parrot based on environmental variables and key resources (breeding) or the species' occurrence (nonbreeding). Pino blanco (Podocarpus parlatorei) seeds are critical food for Tucuman Parrot nestlings, so we modeled the distribution of this tree as a proxy for potential breeding habitat. We then examined the adequacy of current habitat protection relative to representation targets and in light of known threats, including forest degradation and loss, and poaching. Overall, 17% of the 110,122 km2 Southern Yungas is protected, which is close to the proportion recommended (the target; 22%), based on the ecoregion's size, for inclusion in a conservation network. Similarly, 26% of the 46,263 km2 of nonbreeding habitat is protected, also relatively successful at 71% of the target (36%). However, of the scant ~21,000 km2 of breeding habitat, only 15% is protected, much less than the representation target (49%) recommended for maximizing the probability of population persistence. Poaching of nestlings further undermines the value of some nesting habitat in Bolivia. For Tucuman Parrots, increased enforcement of protection in Bolivia and protection of additional nesting habitat in Argentina are the most efficient ways to enhance persistence. Our results illustrate how habitat conservation targets based on area alone may be inadequate if important biological information is overlooked.